Convergence of Forked Sequence to a Fixed Point in Modular Function Spaces - Salman, Bareq Baqi; Abed, Salwa Salman (Iraqi Journal of Science, 2024)
In this paper, we present a five-step iterative scheme, at the beginning, it seems complicated and difficult to implement, but in fact it’s not. This scheme is constructed for - firmly nonexpansive mappings in modular function spaces. Two different -convergences result has been proved for double schemes under consideration. In our study there is a comparison between these cases through answering the question "which one is faster?” Finally, numerical examples are given by using MATLAB software program.